HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PSYCHOLOGICAL WELL-BEING PADA KARYAWAN DI CV. FORWARD KEDIRI - Sasmita, Sherli; Budiani, Meita Santi (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Employees at distribution companies such as CV. Forward Kediri face various workplace dynamics, including sales target pressures, customer complaints, and intense industry competition, all of which can impact their psychological condition. These challenges demand that employees possess strong mental resilience and adequate emotional support to remain productive. This study aims to examine the relationship between social support and psychological well-being among employees at CV. Forward Kediri. A quantitative research method was employed using a saturated sampling technique, involving 85 employees as respondents. Data were collected using questionnaires based on a social support scale and a psychological well-being scale. Hypothesis testing was conducted using the Pearson Product-Moment correlation, assisted by SPSS version 22.0 for Windows. The results indicated a significance value of 0.000 (p < 0.05) and a correlation coefficient of 0.706, demonstrating a strong and positive relationship between social support and psychological well-being. This suggests that the higher the level of social support received by employees, the higher their psychological well-being. ABSTRAK Karyawan di perusahaan distributor seperti CV. Forward Kediri menghadapi berbagai dinamika kerja seperti tekanan target penjualan, komplain pelanggan, dan persaingan industri yang ketat yang dapat memengaruhi kondisi psikologis mereka. Tantangan ini menuntut karyawan memiliki ketahanan mental dan dukungan emosional yang memadai agar tetap produktif. Penelitian ini dimaksudkan untuk mengidentifikasi hubungan antara dukungan sosial dengan psychological well-being pada karyawan di CV. Forward Kediri. Penelitian ini menggunakan metode kuantitatif dengan teknik sampling jenuh dan melibatkan 85 karyawan sebagai sampel. Instrumen pengumpulan data dalam bentuk kuesioner dengan skala dukungan sosial serta skala psychological well-being. Uji hipotesis dilakukan menggunakan korelasi Pearson Product Moment dengan bantuan SPSS versi 22.0 for Windows. Hasil penelitian menunjukkan nilai signifikansi sebesar 0,000 (p<0,05) dan koefisien korelasi sebesar 0,706, yang menunjukkan bahwa dukungan sosial dengan psychological well-being mempunyai hubungan pada kategori kuat dan positif sehingga semakin tinggi dukungan sosial yang diterima karyawan, maka semakin tinggi pula psychological well-being yang mereka miliki.